Composite materials - Sharma, S. C. (Narosa Publishing House, 2000)
This book covers all the aspects of compoiste materials and concepts of composite technology. Beginning with various types of composites being currently used, it explains in depth, various matrix materials and reinforcements which combine to form different types of composites and the factors contributing their selection ; design of composite materials ; factors governing matrix and reinforcement, selection and other processing techniques. The concept of PMCs, CMCs and carbon-carbon composites with specific emphasis on the future applications of composites and its technology are discussed in detail.